Improving QOS In WLAN Using Dynamic Weighted Fair Scheduling - Riza, Ahmed; Chaw, Ling Teck; Keong, Phang Keat; Pee, Hoh Kian (Malaysian Journal of Computer Science, 2017)
The demand for end-to-end Quality of Service (QoS) in Wireless Local Area Networks (WLANs) is becoming ever more important due to the trend towards converged communication networks. The recently accepted QoS mechanism in WLAN; the IEEE 802.11e has limitations in providing fairness to different types of traffic. We propose Dynamic Weighted Fair Scheduling Scheme (DWFSS) to improve fairness in WLANs by enhancing the IEEE 802.11e. The DWFSS allocates bandwidth to four different classes of traffic. These classes are assigned weights which are dynamically changed. The service interval in IEEE 802.11e is divided into two intervals i.e., High Priority Polling Interval (HPPI) and Low Priority Polling Interval (LPPI). The high priority traffic is polled during HPPI and low priority traffic is polled during LPPI. The performance of DWFSS is evaluated on NCTUns simulator using multiple types of traffic and compared with the standard scheduler. The simulation results showed that DWFSS improved fairness when compared to IEEE 802.11e standard scheduler. DWFSS increased average throughput by 13.48% and reduced average jitter by 16.21% while maintaining an acceptable level of end-to-end delay.